Comparison of Antioxidant Effectiveness of Papaya Leaf Extract and Bidara Leaf Extract Using the DPPH Method: A Literature Review - Hilmah Ayu Mardhiyya; Dia Septiani; Muhammad Rofif Albukhori (Jurnal Biologi Tropis, 2026)
Natural antioxidants have gained increasing attention as safer alternatives to synthetic antioxidants for preventing oxidative stress caused by free radicals. Papaya (Carica papaya L.) and bidara (Ziziphus sp.) leaves are rich in bioactive compounds, including flavonoids, phenolics, vitamin C, and vitamin E, which exhibit antioxidant properties. This study aimed to compare the antioxidant activity of papaya and bidara leaf extracts based on evidence from published studies using the DPPH assay. A systematic literature review was conducted by searching the Google Scholar and PubMed databases using predefined keywords and inclusion criteria. A total of 989 records were identified, and 13 eligible articles were included in the final synthesis. The reviewed studies consistently demonstrated that papaya leaf extract exhibited very strong antioxidant activity, particularly in topical formulations such as creams and emulgels, with lower IC₅₀ values indicating greater free-radical scavenging capacity. In contrast, bidara leaf extract showed moderate to strong antioxidant activity, with IC₅₀ values ranging from 90 to 263 ppm, depending on the extraction solvent and method employed. Overall, papaya leaf extract demonstrated a stronger and more consistent antioxidant profile than bidara leaf extract. These findings suggest that papaya leaves have greater potential as a natural antioxidant source, while further in vivo and clinical studies are needed to validate their therapeutic applications.